Sunset eating up the West Coast : the best road trips, restaurants, and recipes from California to Washington - Binns, Brigit Legere (Time Home Entertainment Inc., 2015)
Sunset Magazine and cookbook author and Road Foodie blogger Brigit Binns team up to take readers on a mouthwatering tour along scenic highways and picturesque back roads of the Pacific coast. Brigit and her trusty canine companion, Stella, make their way up the region in four bites--Southern California, Northern California, Oregon, and Washington--discovering local eateries, dives, and cafes that showcase the true flavors of each region. More than 125 delicious and authentic recipes fill the pages of this part cookbook, part delicious journey, along with tales from owners, patrons, and employees that bring each restaurant's and region's personality to light. Impeccable full color photography also graces the pages, taking readers both inside these landmark gems and outside to the surrounding scenery.